Rapidly obtaining genome sequence of Severe Fever with Thrombocytopenia Syndrome virus directly from clinical serum specimen using long amplicon based nanopore sequencing workflow - Tingting Tian; Yanhan Wen; Liping Gao; Tiezhu Liu; Xiaoxia Huang; Chuan Li; Shanshan Du; Hao Li; Meijun Guo; Jiandong Li; Shiwen Wang; Dexin Li; et al. (PLoS ONE, 2025)
Severe Fever with Thrombocytopenia Syndrome (SFTS) is an emerging viral infectious disease discovered in 2009 with a high fatality rate and continuing to pose a public threat for many countries. Surveillance of genome sequence of its causative pathogen, Severe Fever with Thrombocytopenia Syndrome virus (SFTSV), could provide evidence for SFTS control, diagnosis method update, viral evolution dynamic and pathogenic mechanism research, etc. Here, we developed a workflow for rapidly obtaining the genome sequence of SFTSV directly from clinical samples to facilitate the viral genome sequence surveillance. Three pairs of primers targeting the terminal conserved regions of three segments were newly designed to more efficiently enrich nearly whole viral genome. Datasets comprised reads generated in different timeframes for four simulated samples with high to low serially diluted viral loads were subjected to analysis. For a simulated sample with a Ct value of 35 and sequenced for 10 minutes, the average coverage depth could reach over 700x, and the genome coverage could reach 98.69% after subtraction of the primer sequence, and the sequence identity with Sanger sequencing could reach over 99.91%. Two clinical serum specimens were used to validate the workflow and sequences were successfully obtained. A long amplicon based nanopore sequencing workflow was established, which could finish in 10 hours from serum specimen to genome sequence. This workflow has potential to provide essential information for SFTS control and support further pathogenesis research.